2008
DOI: 10.1002/biof.5520340205
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative damage markers and antioxidants in patients with acute myocardial infarction and their clinical significance

Abstract: Oxidative stress has been associated with degenerative diseases such as cardiovascular and neurodegenerative diseases. Acute myocardial infarction (AMI) is the major cause of death among cardiovascular diseases. Inflammation, a major risk factor of AMI, is associated with leukocytic activation, secretion of myeloperoxidase (MPO) and subsequent oxidant generation. It has been hypothesized that oxidative stress is a risk factor for AMI. To test this hypothesis, we studied profiles of oxidative damage and antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
1
1
0
Order By: Relevance
“…This meta-analysis, by pooling together 14 studies enrolling 810 CVD patients and 1106 controls, has allowed to further address this issue. Moreover, two studies by Ho et al ( 14 ) and Kaya et al ( 19 ), not included in the present meta-analysis because they performed the evaluation of DNA damage in DNA extracted from white blood cell and expressed the ratio between 8-OHdG and 10 6 dG ( Supplementary Table S1 ), widely confirmed our results. When pooling together data from these two studies, we found higher levels of 8-OHdG in the 154 CAD patients than in the 97 controls (SMD: 1.79, 95% CI: 1.49–2.09, p < 0.001, I 2 : 0%, p = 0.45).…”
Section: Discussionsupporting
confidence: 83%
“…This meta-analysis, by pooling together 14 studies enrolling 810 CVD patients and 1106 controls, has allowed to further address this issue. Moreover, two studies by Ho et al ( 14 ) and Kaya et al ( 19 ), not included in the present meta-analysis because they performed the evaluation of DNA damage in DNA extracted from white blood cell and expressed the ratio between 8-OHdG and 10 6 dG ( Supplementary Table S1 ), widely confirmed our results. When pooling together data from these two studies, we found higher levels of 8-OHdG in the 154 CAD patients than in the 97 controls (SMD: 1.79, 95% CI: 1.49–2.09, p < 0.001, I 2 : 0%, p = 0.45).…”
Section: Discussionsupporting
confidence: 83%
“…Ho et al reported that the levels of the oxidative markers as 8-hydroxydeoxyguanosine (8-OHdG) and myeloperoxidase (MPO) were significantly higher and that the antioxidant capacity (measured as GPD and vitamin E) was significantly lower in patients with MI (17). In a recent study by Lo Presti et al, oxidant products were significantly higher, and antioxidant products were significantly lower in patients under 45 years old with AMI than in the control group (18).…”
Section: Discussionmentioning
confidence: 99%